2017
DOI: 10.1039/c7ra01840a
|View full text |Cite
|
Sign up to set email alerts
|

CuCo2O4nanowire arrays supported on carbon cloth as an efficient 3D binder-free electrode for non-enzymatic glucose sensing

Abstract: CuCo 2 O 4 nanowire arrays supported on carbon cloth (CuCo 2 O 4 NWAs/CC) were prepared via a simple hydrothermal synthesis and subsequent calcination process. As a 3D binder-free electrode for nonenzymatic glucose sensing, CuCo 2 O 4 NWAs/CC shows high sensing performance towards glucose under alkaline conditions, with a wide detection range from 1 mM to 0.93 mM, a low detection limit of 0.5 mM (S/N ¼ 3), and a high detection sensitivity of 3.93 mA mM À1 cm À2. Moreover, CuCo 2 O 4 NWAs/CC shows good selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 44 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…4,[6][7][8][9] Different kinds of materials have been applied to construct nonenzymatic glucose sensors including metals, alloys, metal oxides, and carbon. [10][11][12][13][14][15] Among all kinds of materials, nanostructure metals are one of the most potential ones since they can supply more surface active sites and exhibit much higher catalytic performance. [16][17][18][19][20] Nanostructure gold has received much attention due to its high catalytic activity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][9] Different kinds of materials have been applied to construct nonenzymatic glucose sensors including metals, alloys, metal oxides, and carbon. [10][11][12][13][14][15] Among all kinds of materials, nanostructure metals are one of the most potential ones since they can supply more surface active sites and exhibit much higher catalytic performance. [16][17][18][19][20] Nanostructure gold has received much attention due to its high catalytic activity and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the redox peak may be correlated with the irreversible transition between CoO and CoOOH and between CoOOH and CoO 2 respectively. The electrochemically reversible redox reactions in the alkaline medium can be formulated as follows : trueCuO@Co3normalO4+OH-+normalH2normalOCuOOH+3CoOOH+normale- trueCoOOH+OH-CoO2+normalH2normalO+normale- …”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that MOF Co 3 O 4 anchored on the surface of CuO NWs showed excellent electrocatalytic activity and play a crucial electrochemical nano‐enzymatic glucose sensor. According to the previous reports the possible mechanism of the electrochemical oxidation of glucose is proposed as follows: true24ptCo3normalO4+normalC6normalH10normalO62CoOOH+normalC6normalH10normalO6(gluconolactone) trueCoOOH+normalC6normalH10normalO6Co(OH)2+normalC6normalH10normalO6 trueCuOOH+normalC6normalH10normalO6Cu(OH)2+normalC6normalH10normalO6 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations